Characterization of the Mutational Signature of Formaldehyde to Elucidate Its Role in Carcinogenesis - Fabros, Reena Michelle (Université d'Ottawa / University of Ottawa, 2020)
Cancer is a genetic disease caused by the accumulation of multiple mutations in essential genes controlling normal proliferation. Genomic analysis of cancer samples revealed that somatic mutations form distinct patterns on the DNA called mutational signatures, which were produced by different mutational processes that have been operative throughout the development of a cancer cell. Out of 77 deciphered mutational signatures from cancer genomes, 29 of them have unknown aetiologies. The current strategy to elucidate these unknown signatures is through mutational signature characterization of various mutagens from model systems. One such mutagen with an ambiguous mutational signature is formaldehyde. This work describes the first specific characterization of the mutational patterns induced by formaldehyde. Using yeast genomics data, formaldehyde mutagenesis was shown to form C→A transversions over TCn trinucleotide motifs. Moreover, it induces an excess of single nucleotide indels with a preference for adenine insertions and cytosine deletions. Due to a limited sample size, the contribution of formaldehyde mutagenesis in relevant cancers cannot be accurately depicted, however, the formaldehyde-specific pattern of C→A transversions can be observed from these cancer genomes. These results ultimately present a likely mechanism for formaldehyde mutagenesis on the nucleotide bases.
Keywords: formaldehyde; mutational signature; cancer; mutations; genomics; budding yeast